Does maintaining bindings in visual working memory require more attention than maintaining features?. Issue 6 (3rd July 2019) - Che, Xiaowei; Ding, Xiaowei; Ling, Xiaoli; Wang, Hailing; Gu, Yuanyuan; Li, Shouxin
ABSTRACT: Whether more attention is required for maintaining bindings than maintaining features in visual working memory (VWM) remains an open question. If maintaining bindings in VWM does not require more attention than maintaining features, is it related to the stability of binding representations? In this study, we explored whether maintaining bindings requires more attention than maintaining features for similar and dissimilar objects by inserting a feature report task into the maintenance phase of VWM in Experiments 1 and 2. We also investigated whether the effect of similarity on the attentional requirement for maintaining bindings and features is due to the stability of VWM representations by inserting a suffix during the maintenance phase of VWM in Experiment 3. The results showed that when object-based attention was consumed, bindings were more impaired than features for dissimilar objects but not for similar objects. We also found that the bindings of similar objects were less interfered by the suffix than those of dissimilar objects. Our findings suggest that maintaining bindings does not require more attention than maintaining features when the binding representations are stable in VWM and similarity improves the stability of binding representations.